Integrating Video Tutorials to Overcome Learning Challenges in Basic Electronics at Vocational High Schools - Abdul Rahmanto; Fadhli Ranuharja; Amir Karimi (Departement of Electrical Engineering Universitas Negeri Padang, 2025)
This research presents strong evidence supporting the effectiveness of video tutorial media in improving student learning outcomes within vocational education. By delivering content in a visually appealing and organized manner, video tutorials enhance student engagement and deepen conceptual understanding, especially in technical subjects. The study applied a quasi-experimental design with a descriptive quantitative approach to assess the influence of video tutorials on student performance in the Basic Electronics course. The participants included 45 tenth-grade students from the Industrial Electronics Engineering (TEI) program at SMKN 4 Pariaman. Data were gathered through post-test results and analyzed using an independent sample t-test to evaluate statistical differences between the experimental group (utilizing video tutorials) and the control group (employing traditional teaching methods). The findings indicated that students who used video tutorial media achieved significantly higher academic results than those taught through conventional approaches. These results highlight the potential of video-based instructional tools to support effective and modern teaching strategies in vocational schools. Moreover, the integration of such media not only boosts academic achievement but also encourages student independence and active involvement in hands-on learning experiences